Probing darking energy through gass mass fraction - Barbosa, Dinorah; von Marttens, Rodrigo; Gonzalez, Javier; Alcaniz, Jailson (Cadernos de Astronomia, 2026)
We explore the possibility of breaking the dark degeneracy by using measurements of the gas mass fraction observed in massive and relaxed galaxy clusters. This data is particularly interesting for this purpose because it isolates the matter contribution, possibly allowing the degeneracy breaking. We study the particular case of the wCDM model with its interactive counterpart. We compare the results obtained from both descriptions with a non-parametric analysis obtained through Gaussian Process. Even though the degeneracy may be broken from the theoretical point of view, we find that current gas mass fraction data seems to be insufficient for a final conclusion about which approach is favored, even when combined with SNIa, BAO and CMB.
Keywords: cosmology; dark energy; dark matter; gas mass fraction